Flow Akademik dan Prokrastinasi Akademik - Hidayati, Nuril; Al-Akhda Aulia, Lailatuzzahro (Fakultas Psikologi Universitas Yudharta Pasuruan, 2019)
Procrastination is behavior that is often carried out in everyday life. One of them is in the wor ld of education, where the students deliberately delaying to begin or complete the tasks assigned in school or so-called academic procrastination. Students often do it because, they are waiting for the right time to work with focus and uncomfortable study flow academic or not conditions. Academic procratination scale with coefficient of pearson product moment correlation betwen 0,303 to 0,638 and coefficient of reliability 0,899 and to scale the flow academic 0,313 to 0.681 with a reliability coefficient of 0.93. Thus, all the scale is reliable to use. This study uses 120 students were selected by stratified random sampling of 759 students. The regression analysis of predictors obtained Freg value of 8.319. Thus, there is a highly significant relationship between academic procrastination with academic flow. Flow academic influence forming 6.59% of the academic procrastination behavior. Thus, it can be concluded that the hypothesis that there is a relationship between acadeic with academic procrastination accepted at significance level of 1%, which amounted to -0.257 r xy is greater than can be predid r table 5%. This means that the higher academic flow conditions of the students, the lower academic procrastination behavior of the student, and vice versa when the high academic procrastination behavior so low flow academic.